Human rights, human development, and peace: inseparable ingredients in Africa's quest for prosperity - Eno, Robert W. (My University, 2009)
Despite decades of foreign aid, abundance of natural and human resources, and numerous development initiatives, the African continent remains largely underdeveloped, marginalised and excluded from major decision-making processes that shape today’s world. The purpose of this research is to examine the reasons for the continuous underdevelopment and marginalisation of the African continent and to advance pragmatic measures to be put in place to reverse the situation. The thesis demonstrates that Africa’s underdevelopment and marginalisation cannot be divorced from the effects of centuries of exploitation, domination, and exclusion through the slave trade, colonialism, and neo-colonialism on the one hand, and decades of poor socio-economic and political governance that have characterised the continent since independence, on the other. One of the main findings of the research is that, over the years, African leaders have consciously or unconsciously failed to recognise the fundamental link between human rights, human development, and peace as a foundation for development, and this failure has resulted in their inability to craft sustainable development initiatives for the continent. Given the prominent place human rights, good governance, democracy, peace and stability occupy in both the Constitutive Act of the African Union (CA-AU)1 and the New Partnership for Africa’s Development2 (referred throughout this thesis as the NEPAD Document), the thesis further demonstrates that there is an intrinsic relationship between human rights, human development, and peace which is necessary for development. It analyses the extent to which this relationship has been taken into account in 1 The Constitutive Act of the African Union, OAU Doc. CAB/LEG/23.15, was adopted 11 July 2000 in Lomé, Togo and entered into force May 26, 2001. 2 The New Partnership for Africa's Development (NEPAD or the NEPAD Document) 2001. The NEPAD is an economic development program of the African Union. The NEPAD was adopted at the 37th Session of the Assembly of Heads of State and Government in July 2001 in Lusaka, Zambia. PhD Thesis Human Rights, Human Development and Peace – inseparable ingredients in Africa’s quest for prosperity xvi the conception, formulation, and implementation of the objectives of both the AU and the NEPAD; and concludes that the NEPAD and the AU initiatives provide a strong foundation and offer an excellent opportunity for Africans to begin to reverse centuries of exploitation, domination, and decades of socioeconomic and political exclusion, as well as re-orientate the governance and development strategy of the continent. The thesis is premised on the realisation that respect for human rights, the promotion of human development, and the consolidation of peace, coupled with good political and economic governance are conditions sine qua non for any meaningful development. It further reveals that respect for human rights provides a foundation upon which rests the political structures of human freedoms. The achievement of human freedom generates the will as well as the capacity for economic and social progress. The attainment of economic and social progress provides the basis for durable peace. The thesis concludes that human rights, human development, and peace are interdependent, interrelated, indivisible and mutually reinforcing, and thus inseparable ingredients in Africa’s quest for prosperity.
Keywords: Human rights; Human development; Underdevelopment; Peace